Characteristics of Menopause in Women with Vitamin D Deficiency - Amonova Madina Furkatovna; Sattorova Matluba Akbar kizi (Journal of Science in Medicine and Life, 2024)
Cesarean delivery is one of the oldest surgical operations. There are many indications for its implementation. The main goal of the manipulation is to save the health and sometimes the life of the mother and the baby; In our reality, a caesarean section is performed strictly according to the instructions, and after the operation, doctors continue to carefully monitor the woman's well-being and recovery processes in her body. After all, this operation seems very simple, and despite the fact that medical technology is constantly improving, it is still a surgical intervention. Of course, the recovery process after a natural birth and after a cesarean birth is different. During childbirth, many changes occur in a woman's body, for which nature has prepared an expectant mother during pregnancy. These are various changes in the cardiovascular, endocrine, respiratory systems, blood clotting system and others. Some of these changes are activated during cesarean delivery, while others follow a different scenario.